A SCOPING REVIEW OF DIGITAL AGRITOURISM IN RURAL DEVELOPMENT FUTURES - Ahmad, Siti Yuliandi; Johari, Arina; Hama, Susan (Malaysian Consumer and Family Economics Association, 2025)
The intersection between agritourism, rural development, and digital innovation has attracted increasing scholarly interest in recent years, particularly as rural destinations adopt digital tools to shape tourist decision-making and enhance experiential value. As agritourism evolves beyond traditional farm visits, it increasingly becomes a site of digital consumption where visitors engage with online information, social media content, and technology-enabled services that influence their perceptions, expectations, and co-created experiences. However, academic literature remains fragmented in linking these developments to consumer behaviour and digital consumer welfare, particularly in emerging economies. This scoping review synthesises global and Malaysian agritourism studies published between 2023 and 2025, with emphasis on how digitalisation mediates tourist experience, perceived value, and participatory roles within agritourism ecosystems. Following the Arksey and O’Malley framework and PRISMA-ScR protocol, twenty-one peer-reviewed sources were systematically analysed. The review identifies four dominant patterns: (1) digital adoption remains uneven, constraining consumer access and limiting trust in digital touchpoints; (2) innovation is often discussed without connecting it to consumer value creation; (3) empirical work is concentrated in a few national contexts, limiting generalisability of consumer insights; and (4) ASEAN perspectives remain underrepresented in digital consumer debates. The review concludes that agritourism scholarship would benefit from deeper integration of consumer behaviour theories, digital experience models, and welfare-oriented perspectives to understand how digital tools reshape visitor engagement in rural environments. The study contributes a multi-level agenda for consumer-centred agritourism research, highlighting implications for digital experience design, rural enterprise strategy, and inclusive tourism development in digitally transitioning regions.